Topographic Cues Impact on Embryonic Stem Cell Zscan4-Metastate - Natale, Carlo F.; Angrisano, Tiziana; Pistelli, Luigi; Falco, Geppino; Calabrò, Viola; Netti, Paolo A.; Ventre, Maurizio (Frontiers in Bioengineering and Biotechnology, 2020)
The extracellular microenvironment proved to exert a potent regulatory effect over different aspects of Embryonic Stem Cells (ESCs) behavior. In particular, the employment of engineered culture surfaces aimed at modulating ESC self-organization resulted effective in directing ESCs toward specific fate decision. ESCs fluctuate among different levels of functional potency and in this context the Zscan4 gene marks the so-called “metastate”, a cellular state in which ESCs retain both self-renewal and pluripotency capabilities. Here we investigated the impact of topographic cues on ESCs pluripotency, differentiation and organization capabilities. To this aim, we engineered culturing platforms of nanograted surfaces with different features size and we investigated their impact on ESCs multicellular organization and Zscan4 gene expression. We showed that the morphology of ESC-derived aggregates and Zscan4 expression are strictly intertwined. Our data suggest that ESC Zscan4 metastate can be promoted if the adhesive surface conditions guide cellular self-aggregation into 3D dome-like structure, in which both cell-material interactions and cell-cell contact are supportive for Zscan4 expression.